16. Investigation of the Auditory Steady State Response in Schizophrenia, Schizoaffective, Psychotic and Nonpsychotic Bipolar Disorders - Parker, David (Schizophr Bull, 2017)
Background: Electroencephalographic (EEG) studies of the auditory steady state response (aSSR) noninvasively probe oscillatory capacity and synchronization in the primary auditory cortex. Abnormalities in the aSSRs have been proposed as translational biomarkers for schizophrenia. However, few studies have examined the aSSRs across diagnostic categories and included the full spectrum of psychotic subgroups (Schizophrenia: SZ, Schizoaffective disorder: SAD, Bipolar disorder with psychosis: BDP, and Bipolar disorder without psychosis: BD-NP). This is a critical step to determine its utility as a potential biomarker and to provide insight into specific neural dysregulations related to psychotic etiology. In this study, auditory steady state stimuli were administered to a large sample of well-characterized participants diagnosed with SZ, SAD, BDP, or BD-NP. Methods: 501 individuals (HC = 184, SZ = 91, SAD = 97, BD-WP = 79, BD-NP = 50) completed aSSRs EEG task at the 5 BSNIP research sites. 1500ms broadband noise sequences modulated at 20, 40, or 80-Hz were presented to investigate neural responses related to distinct frequency bands. Intertrial phase coherence (ITC) was calculated for each subject and sensor resulting in time–frequency values ranging from 5 to 90-Hz and 500–2000 ms. An average aSSR was created using the average of the 7 peak sensors and the 0–1500ms period for each subject. 1-way ANOVAs were completed for each frequency of interest and follow up Welch’s t-tests were performed to compare group differences. Results: SZ and SAD had significantly reduced ITC for all three frequency conditions in comparison to HC and BD-NP. BDP was reduced in the 20 and 40-Hz conditions in comparison to HC, but not in the 80-Hz condition. BDP differed from BD-NP only in the 40-Hz condition. HC and BD-NP did not significantly differ in any of the frequency conditions. Conclusion: Three main conclusions can be drawn from this study. (1) All 3 psychotic subgroups (SZ, SAD, and BDP) had reduced ITC in comparison to HC and BD-NP at 40-Hz. This suggests that the 40-Hz aSSR indexes psychosis in general and is not a SZ specific response. (2) SZ and SAD both showed significant reductions in the 80-Hz aSSR. This suggests that these psychotic subgroups significantly differ in their high-gamma response, which could potentially be related to a difference in pathophysiology and the severity/noncyclical nature of their psychotic symptomology. (3) BD-NP did not significantly differ from HC in any of the aSSR conditions. This could explain the mixed findings in the literature of the aSSR response in bipolar disorder and suggests that future biological-based research should consider distinguishing these groups. Examining differences in the aSSR between proband groups offers unique insight into how neural synchronization relates to the etiology of major psychotic disorders and provides novel evidence about its use as a translational biomarker.